A novel approach to analyse combined pre and post strain rate dependent phase transformation in uniaxially deformed AISI 304 stainless steel using XRD and EBSD. Issue 2 (17th January 2022) - Dey, S.; Gayathri, N.; Mukherjee, P.; Dutta, Argha; Mitra, Manoj Kumar
ABSTRACT: The effect of pre-strain, pre-strain rate and post-strain rates on the deformation-induced austenite to martensite phase transformation have been studied in AISI 304 stainless steel. The martensite content obtained from the X-ray diffraction analysis and complemented by the magnetisation measurements showed that the phase transformation is enhanced for a unique combination of pre-strain, pre-strain rate and post-strain rate. The microstructural characterisation using detailed X-ray diffraction line profile analysis in terms of the size of the coherently scattering region and the dislocations that cause the microstrain within this region could give evidence of the enhanced/reduced martensite formation. The results of the electron backscattered diffraction in terms of the angular distribution of the lattice correlation boundaries and the orientation relationship boundaries of the austenite-martensite phase substantiated this finding. Considering that the multiple combinations of deformation parameters control the mechanism of martensitic transformation, this study will also contribute to the understanding of deformation-induced phase transformation of other materials with improved plasticity.